2012
DOI: 10.1007/s11033-012-2186-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed C-type natriuretic peptide serves as an early compensatory response to counteract extracellular matrix remodeling in unilateral ureteral obstruction rats

Abstract: Although the mechanism underlying C-type natriuretic peptide (CNP) beneficial effects is not entirely understood, modulating the expression of matrix metalloproteinases (MMPs)/tissue inhibitors of metalloproteinases (TIMPs) may play an important role. The study presented herein was designed as a first demonstration of the regulative effects of CNP on MMPs/TIMPs expression in unilateral ureteral obstruction (UUO) rats. The continuous changes of CNP, MMP-2, MMP-9, TIMP-1, TIMP-2 and type IV collagen (Col-IV) exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…One common mechanism underpinning the development of atherosclerosis and aneurysm is the activation of MMPs, particularly MMP-2 and MMP-9 (57)(58)(59). This may be a key point of intervention of endothelium-derived CNP, since in chondrocytes, CNP overexpression reverses achondroplasia by reducing the activity and release of several MMPs, including both MMP-2 and MMP-9 (60), and CNP regulates the MMP/tissue inhibitors of metalloproteinases (TIMP) ratio to ameliorate renal fibrosis following ureteral obstruction (61). Our work might therefore explain the beneficial activity of neutral endopeptidase inhibitors, which prevent the endogenous breakdown of CNP (and other natriuretic peptides), in experimental models of atherosclerosis (62).…”
Section: Methodsmentioning
confidence: 99%
“…One common mechanism underpinning the development of atherosclerosis and aneurysm is the activation of MMPs, particularly MMP-2 and MMP-9 (57)(58)(59). This may be a key point of intervention of endothelium-derived CNP, since in chondrocytes, CNP overexpression reverses achondroplasia by reducing the activity and release of several MMPs, including both MMP-2 and MMP-9 (60), and CNP regulates the MMP/tissue inhibitors of metalloproteinases (TIMP) ratio to ameliorate renal fibrosis following ureteral obstruction (61). Our work might therefore explain the beneficial activity of neutral endopeptidase inhibitors, which prevent the endogenous breakdown of CNP (and other natriuretic peptides), in experimental models of atherosclerosis (62).…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] Our latest study published in Molecular Biology Reports revealed that CNP expression was markedly increased in the obstructed kidneys as early as three days post-ligation. 8 An expansion of extracellular fluid volume may contribute to the locally synthesized CNP. However, it should be noted that our previous study was not carried out for long enough to examine the continuous change of CNP during the entire time course of experimental obstructive nephropathy and, to date, the association of CNP expression with its receptors and NEP in the obstructed kidneys is poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral ureteral obstruction (UUO) is a well-established model known to imitate the process of obstructive nephropathy in a simple, accelerated and species-independent manner 1. Previous studies from our laboratory and others demonstrate that the morphological lesions in the obstructed kidney are characterized by peritubular capillaries rarefaction, tubular atrophy, inflammatory infiltration, widen interstitial space, and progressive tubulointerstitial fibrosis 2, 3. In addition, compensatory hypertrophy of the contralateral kidney is another typical feature in the UUO model 4.…”
Section: Introductionmentioning
confidence: 99%